2018
DOI: 10.1111/are.13661
|View full text |Cite
|
Sign up to set email alerts
|

Does the wild-caught Chinese mitten crab megalopae perform better than the hatchery-produced seed during the juvenile culture?

Abstract: Although wild Yangtze Eriocheir sinensis juveniles (coin‐sized seed) have better culture performance than the pond‐reared juveniles during the adult crab culture stage, the culture performance of wild‐caught megalopae (WC) remains unknown. Therefore, this study was designed to compare the growth, survival rate, crab yield, feed conversion rate (FCR), precocity, final weight and size distribution between WC and hatchery‐produced megalopae (HP) during the juvenile culture stage. Wild‐caught megalopae had signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Previous studies suggested lower productivity among the hatchery-produced crabs than their wild counterparts, fish and various invertebrate species ( Bannister et al., 1994 ; Malavasi et al., 2008 ; Swain and Riddell, 1990 ). Besides, it had also been suggested that the hatchery-reared crablets could exhibit comparable or better performance than wild-sourced crablets ( del Mar Gil et al., 2019 ; Ut et al., 2007 ; Wu et al., 2018 ). Nonetheless, the performance of the hatchery-reared crablets might vary depending on the production batch due to the interaction between genetic makeup and environmental factors ( Tweedley et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested lower productivity among the hatchery-produced crabs than their wild counterparts, fish and various invertebrate species ( Bannister et al., 1994 ; Malavasi et al., 2008 ; Swain and Riddell, 1990 ). Besides, it had also been suggested that the hatchery-reared crablets could exhibit comparable or better performance than wild-sourced crablets ( del Mar Gil et al., 2019 ; Ut et al., 2007 ; Wu et al., 2018 ). Nonetheless, the performance of the hatchery-reared crablets might vary depending on the production batch due to the interaction between genetic makeup and environmental factors ( Tweedley et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The initial body weight of experimental crabs was set within the range of 70 g to 90 g, which is the typical weight of adult female crabs that have recently completed puberty moulting. The maturation of adult crabs was determined based on their secondary sex characteristics as descript by Wu et al [42]. After 5 days of domestication in the tank, lively and whole crabs were selected for subsequent culture.…”
Section: Diet Formulation and Preparation As Shown In Tablementioning
confidence: 99%
“…Annual aquaculture production of E . sinensis in China increased from 8000 t in 1991 to approximately 775,900 t in 2020, with further increases anticipated in the future (Bureau of Fisheries & Management, 2020; Wu et al, 2018). When maintained in earthen ponds in the Yangtze River basin, E .…”
Section: Introductionmentioning
confidence: 99%
“…Given its delicate flavour and high nutritional value, as well as advances in hatchery and grow-out techniques, the aquaculture of E. sinensis has undergone a rapid expansion during the past few decades (Cheng et al, 2008). Annual aquaculture production of E. sinensis in China increased from 8000 t in 1991 to approximately 775,900 t in 2020, with further increases anticipated in the future (Bureau of Fisheries & Management, 2020;Wu et al, 2018). When maintained in earthen ponds in the Yangtze River basin, E. sinensis attains physiological maturity in early October and these crabs are marketed after the onset of maturation.…”
mentioning
confidence: 99%